A simple and efficient magnetic solid phase extraction strategy assisted by CoS@polypyrrole@Fe3O4 nanocomposite for determination of palladium in the soil samples - Zeytinci, Nagehan Kubra; Akbiyik, Hilal; Zaman, Buse Tugba; Sahin, Cigdem; Bakirdere, Sezgin (ELSEVIER, 2025)
In the present work, an efficient/simple magnetic solid phase extraction (MSPE) strategy was developed using CoS@polypyrrole@Fe3O4 nanocomposite for the separation/preconcentration of palladium ions. The nanocomposite composed of CoS, polypyrrole, and Fe3O4 (CoS@polypyrrole@Fe3O4) was fabricated using hydrothermal and ultrasonication techniques. The CoS@polypyrrole@Fe3O4-MSPE technique was effectively integrated with the slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) system to achieve the goal of increasing the detection power of the conventional FAAS system. For this aim, the optimum experimental conditions of the developed separation/preconcentration technique were determined by comprehensive univariate optimization studies. In the experimental steps, buffer solution (pH 9.0 borate-HCl buffer solution) was used to adjust the pH of the sample solution, the extraction was occurred by dispersion of 10 mg nanocomposite with the aid of 45 s vortex mixing. At last, desorption was performed by using 75 mu L of 14.4 M HNO3 solution. Afterward, the system analytical performance value was evaluated under the optimum conditions determined. A mass-based detection limit of the analytical system developed was recorded as 0.055 mg/kg which, provides higher detection power for FAAS measurement for palladium ions. Additionally, an accuracy check of the proposed method was performed using soil samples collected from Faure Island, Antarctica. The satisfactory percent recovery results were calculated for the spiked soil samples which, are between 88 and 109 %. The results show that palladium at trace levels can be quantitatively determined and monitored in environmental samples using the MSPE-SQT-FAAS approach.
Keywords: Magnetic solid phase extraction; Nanomaterial; Palladium ions; Preconcentration; PLATINUM; NANOPARTICLES; SORBENT; WATER; MICROEXTRACTION; POLYPYRROLE; SEPARATION; ELEMENTS; RHODIUM; Chemistry